2010
DOI: 10.1007/s11920-010-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

Vocational, Social, and Cognitive Rehabilitation for Individuals Diagnosed With Schizophrenia: A Review of Recent Research and Trends

Abstract: A growing body of evidence suggests that social and vocational interventions effectively enhance social and vocational functioning for individuals with schizophrenia. In this review, we first consider recent advances in vocational and social rehabilitation, then examine current findings on neurocognition, social cognition, and motivation with regard to the impact these elements have on rehabilitation interventions and outcomes. A critical evaluation of recent studies examining standalone treatment approaches a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 76 publications
1
19
0
3
Order By: Relevance
“…Further supporting this recommendation and the clinical relevance of working memory, is that cognitive remediation therapy (CRT) improves neurocognition in schizophrenia (Harvey and Bowie, 2012a;Kurzban et al, 2010), with several studies validating the responsiveness of working memory to these treatments (Lett et al, 2014;Vita et al, 2011). Moreover, research suggests that combining CRT with vocational rehabilitation leads to greater improvements in working memory (Bell et al, 2003) as well as enhanced employment outcomes (McGurk and Wykes, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Further supporting this recommendation and the clinical relevance of working memory, is that cognitive remediation therapy (CRT) improves neurocognition in schizophrenia (Harvey and Bowie, 2012a;Kurzban et al, 2010), with several studies validating the responsiveness of working memory to these treatments (Lett et al, 2014;Vita et al, 2011). Moreover, research suggests that combining CRT with vocational rehabilitation leads to greater improvements in working memory (Bell et al, 2003) as well as enhanced employment outcomes (McGurk and Wykes, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…The vertical dotted line indicates no differences in relapse risk with drug vs. placebo with sound antipsychotic treatment of patients with chronic psychotic disorders. Speci fi c forms of behavioral, educational, and family interventions with a supportive or rehabilitative orientation, in particular, can add substantially to the stability of antipsychotic-treated chronically psychotic patients, often reducing relapse rates by more than 50% compared to drug-alone for up to 2 years [ 109,120,165,217,234 ] . Overall, typical 1-year outcomes in patients diagnosed with schizophrenia average approximately 85% relapse risk without speci fi c treatment, perhaps 5-10% less with a placebo, about 70% relapse risk with psychosocial treatment only, 25% with an antipsychotic drug alone, and perhaps 10% risk with both medicine and psychosocial treatment.…”
Section: Long-term Care Of Psychotic-disorder Patientsmentioning
confidence: 99%
“…Carr (2008) Carr et al (2008) show Q4 that people with ID had greater limitations in terms of autonomy; Mä ä ttä , Tervo-Mä ä ttä , Taanila, Kaski, and Iivanainen (2006) describe greater problems in verbal capacity and Bertoli et al (2011) found that, in people with ID, problems with daily activities increase over time. Moreover, a number of problems arise in daily activities in people with MD, especially in those with severe mental problems (Viertiö et al, 2011;Kurzban, Davis, & Brekke, 2010). So, the functional disability in people with ID-MD is expected to be greater.…”
Section: Q3mentioning
confidence: 99%